Keterbukaan dalam Memahami Esensi al-Qur’an sebagai Kitab Petunjuk (Hudan) dan Penjelas (Tibyanan) dalam Perspektif Pendidikan Islam - Fatih, Muhammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
Science and secular branches of science have been deemed dangerous to the faith, because modern science can only bow its head in respect of the book of Allah and the Sunnah of His Prophet. This paper aims to describe how Openness is in understanding the essence of the Qur'an as a guide (hudan) and an explanation (tibyanan) in the perspective of Islamic education. This research is a qualitative study in library search. Research design is a reflection of the entire research sequence. The activities of collecting and analyzing data, developing and modifying theory, elaborating or focusing research questions, and identifying and dealing with threats to validity all take place more or less simultaneously. From the results of the discussion it can be concluded as follows: 1) In Islamic education, the values ??of the Qur'an are the basic elements of the curriculum and schools cannot but care about educating students without conforming to them. 2) The function of the tibyan al-Qur'an is coupled with the function of "huda" (guidance of faith), because it is very possible that these findings can lead the discoverer to receive guidance, then with his own awareness and choice he acknowledges the greatness of God. 3) In the perspective of Islamic education, the essence of al-Qur'an as a guide (hudan) and an explanation (tibyanan) is the progress of science. Modern science can only bow its head in respect of the book of Allah and the Sunnah of His Prophet.